2021
DOI: 10.1088/1361-6528/abe4f9
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing the efficiency droop in AlGaN-based UVB LEDs

Abstract: The optoelectronic properties of semiconducting aluminum gallium nitride (AlGaN)-based ultraviolet-B (UVB) light-emitting diodes (LEDs) are crucial for real-world medical applications such as cancer therapy and immunotherapy. However, the performance of AlGaN-based UVB LED devices is still poor due to the low hole injection efficiency. Therefore, we have numerically investigated the performance of AlGaN-based UVB LEDs for the suppression of efficiency droop as well as for the enhancement of hole injection in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Consequently, the performance of the UVB LEDs has been deteriorated at RT 4 , 8 , 12 , 23 , 24 , as presented in Table 1 . A reasonable level of 3D hole generation has been successfully realised in the AlGaN/GaN UVC LED by polarisation effect, which is supported by the distribution of Al composition profile from p-AlGaN HSL to the p-GaN contact-layer 33 , 34 , 47 . However, both the p-GaN contact layer and Ni/Au p-electrode can absorb a significant portion of the emitted UV light 8 , 23 .…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Consequently, the performance of the UVB LEDs has been deteriorated at RT 4 , 8 , 12 , 23 , 24 , as presented in Table 1 . A reasonable level of 3D hole generation has been successfully realised in the AlGaN/GaN UVC LED by polarisation effect, which is supported by the distribution of Al composition profile from p-AlGaN HSL to the p-GaN contact-layer 33 , 34 , 47 . However, both the p-GaN contact layer and Ni/Au p-electrode can absorb a significant portion of the emitted UV light 8 , 23 .…”
Section: Resultsmentioning
confidence: 74%
“…It is computed from Eq. ( 1 ) to be about 5 × 10 13 × (x 2 − x 1 ) / d cm −3 , where x 1 and x 2 are the Al compositions at the ends of the graded layer of thickness d (in centimetres) 33 , 46 , 47 . Alongside the [0001]-direction (Ga-polar), the Al composition in the p-Al x Ga 1-x N HSL gradually changes from high Al content of 60% down to low Al content of 40% as observed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although, there has been a significant improvement in fabricating of UV-LEDs with improved quantum efficiencies, both internal and external and with low density of threading dislocations but the effort is still going on to meet the market standards. Muhammad Usman et al numerically investigated AlGaN-based UVB LEDs for the suppression of efficiency droop and got enhanced hole injection in MQWs [ 15 ]. Their numerical simulation suggested that, compared to the conventional structure, the proposed structure had a high peak efficiency and very small efficiency droop.…”
Section: Fabrication Of Duv-ledsmentioning
confidence: 99%
“…This radiation penetrates the skin and is absorbed by 7-dehydrocholesterol (7-DHC) to form cis-cis previtamin D 3 , which undergoes isomerization to produce more thermodynamically stable vitamin D 3 . Several reports have revealed that the hole injection efficiency can be improved in AlGaN-based DUV-LEDs through the functionalization of the p-AlGaN electron-blocking layer (EBL) [ 7 , 23 , 24 , 25 , 26 , 27 , 28 ]. AlGaN-based DUV-LEDs that operate nearly free of efficiency droop have also been prepared [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have revealed that the hole injection efficiency can be improved in AlGaN-based DUV-LEDs through the functionalization of the p-AlGaN electron-blocking layer (EBL) [ 7 , 23 , 24 , 25 , 26 , 27 , 28 ]. AlGaN-based DUV-LEDs that operate nearly free of efficiency droop have also been prepared [ 23 , 24 , 25 ]. Usman et al [ 23 ] found through numerical analysis that the efficiency droop at 500 A cm –2 decreased from 42 to 7% when using an optimized undoped-AlGaN final quantum barrier, a p-type multiple quantum barrier EBL, and an Al composition-graded p-AlGaN hole injection layer in their UVB-LED structure.…”
Section: Introductionmentioning
confidence: 99%